Forum: Reflecting on the Politics of Patrimony. Issue 2 (4th May 2018) - Clarke, Amy; Dewi, Cut; Greenop, Kelly; Mozaffari, Ali; Salma, Khoo; Westbrook, Nigel; Winter, Tim
Abstract: This Forum evolved from a provocation by the Editors of this special issue of Fabrications that "too often heritage conservation assumes an apolitical stance by neglecting to acknowledge its own unsettling agendas." The Forum's five contributors highlight a range of challenges and trends that architectural heritage professionals – including historians – have begun to identify and engage with in a critical fashion. These pieces demonstrate the need to commit to historical practice that embraces the "critical turn, " and to acknowledge our responsibilities as "gatekeepers" and producers of knowledge. While we cannot control the multitude of interpretations that our work will surely generate across time and space, we can consider whether we are contributing to, or challenging, existing silences, inaccuracies, and regimes of knowledge. This Forum does not claim to provide answers, but instead seeks to foster discussion and identify some of the avenues along which work in the general realm of "Architecture / Heritage / Politics" is – or should be – progressing.